Optical and Laser Properties of a Nd doped LaSc3(BO3)4 Crystal - Oh Park, Jun; Oh, Won-Chun; Kweon Jang, Won (Asian Journal of Chemistry, 2012)
We discussed about the single LaSc3(BO3)4 crystal of the high-temperature phase (a-phase), which is a strong candidate for highly doped microchip laser material. The crystal structure of LaSc3(BO3)4, a noncentrosymmetric biaxial crystal, was analyzed with its absorption and fluorescent spectra. The energy levels of a-phased LaSc3(BO3)4 were observed in three main transitions with low temperature spectra to remove the phonon induced homogeneous broadening at different pumping wavelengths. The seven weak oscillation lines and oscillation strengths are investigated in Nd ion doped LaSc3(BO3)4 crystals of 10 and 15 % doped in doping concentration. The fundamental lasing performance of Nd3+:LaSc3(BO3)4 was observed in a hemispherical resonator structure. The various reflectivity of output couplers was used to get the threshold and intra cavity loss. The beam profile of the laser output was also analyzed for cavity volume estimation. The second harmonic generation was performed by using a nonlinear optical crystal of KTP. The Nd3+:LaSc3(BO3)4 crystal has a broad absorption band of 3 nm at 808 nm, the conventional pumping wavelength with commercial diode laser, provide the easy laser operation and the strong oscillation strength at main laser transition proved in this study also attribute the effective microchip laser fabrication.